"Attitudes Towards Languages" (AToL) Scale: A Global Instrument. (March 2013) - Schoel, Christiane; Roessel, Janin; Eck, Jennifer; Janssen, Jana; Petrovic, Branislava; Rothe, Astrid; Rudert, Selma Carolin; Stahlberg, Dagmar
Language attitudes may be differentiated into attitudes towards speakers and attitudes towards languages. However, to date, no systematic and differentiated instrument exists that measures attitudes towards language. Accordingly, we developed, validated, and applied the A ttitudes To wards L anguages (AToL) scale in four studies. In Study 1, we selected 15 items for the AToL scale, which represented the three dimensions of value, sound, and structure. The following studies replicated and validated the three-factor structure and differential mean profiles along the three dimensions for different languages (a) in a more diverse German sample (Study 2), (b) in different countries (Study 3), and (c) when participants based their evaluations on speech samples (Study 4). Moreover, we investigated the relation between the AToL dimensions and stereotypic speaker evaluations. Results confirm the reliability, validity, and generalizability of the AToL scale and its incremental value to mere speaker evaluations.